The digitization of the tramway infrastructure of the Barcelona metropolitan area - Martin Oriol, Jordi; Cabrera Delgado, Eduard (GeoFocus. International Review of Geographical Information Science and Technology, 2023)
This paper presents a general description of the tasks carried out in order to digitalize tram infrastructure in Barcelona’s metropolitan area. Thanks to Geographic Information System tools as complex system tool and spatial representation tool, this paper shows a case of success in the management of a railway infrastructure. Barcelona’s tram infrastructure is configured by two networks, Trambaix and Trambesòs operating since 2004 and did not yet have a genuinely digital infrastructure capable of managing and maintaining assets beyond the As-builts collection released after the commissioning of the infrastructure. Thanks to this project, tram infrastructure can be managed as digital technology in a GIS, BIM and LIDAR environment.